The Mediating Role of SMEs' Performance in the Relationship between Entrepreneur Competence and Satisfaction - Dedi Iskamto; Asyraf Aftanorhan; Puspa liza Ghazali (IQTISHADIA, 2022)
This study aims to examine the mediating role of SME performance in the relationship between entrepreneur competence (EC) and satisfaction (ES) in Indonesia. Data were analyzed using Structural Equation Modeling (SEM), AMOS 24. A total of 380 employers in Pekanbaru City, Riau Province, were selected as the participants. The results showed that SME performance partially mediates the relationship between entrepreneur competence and satisfaction. This is because the direct effect between SMEs' performance and ES is still significant. The implication of this study implies that there is a need to improve the SMEs' performance to increase their competence and create satisfaction for employers. Moreover, entrepreneurs who are satisfied with their businesses always wish to stay longer and do not give up on it.